Răspuns :
A.(x-1)/2=(x+1)/3
3x-3=2x+2
3x-2x=3+2
x=5
B.4*(x+5)=28
4x+20=28
4x=28-20
4x=8
x=2
C.[2*(2x+8)]/16=15
2*(2x+8)=16*15
4x+16=240
4x= 240-16
4x=224
x= 56
3x-3=2x+2
3x-2x=3+2
x=5
B.4*(x+5)=28
4x+20=28
4x=28-20
4x=8
x=2
C.[2*(2x+8)]/16=15
2*(2x+8)=16*15
4x+16=240
4x= 240-16
4x=224
x= 56
C) [2*(2x+8)]/16=15
|·16 ⇒2*(2x+8) =15·16 |:2 ⇒2x+8 =15·8 ⇒
⇒ 2(x+4) = 15·8 |:2⇒ x+4 = 15·4 ⇒ x = 15·4 - 4
B) 4*(x+5)=28 |:4 ⇔ x + 5 = 7 ⇔ x = 7 - 5
⇒ 2(x+4) = 15·8 |:2⇒ x+4 = 15·4 ⇒ x = 15·4 - 4
B) 4*(x+5)=28 |:4 ⇔ x + 5 = 7 ⇔ x = 7 - 5